Mahāyāna Sūtras in Khotan: Quotations in Chapter 6 of the Book of Zambasta (II) - Chen, Ruixuan; Loukota Sanclemente, Diego (Indo-Iranian journal, 2020)
The present paper continues a serial article dealing with the identifications of sources for Chapter 6 of the Book of Zambasta, a Mahāyāna Buddhist poem in Khotanese. The first installment of this serial article was published in 2018 by the same authors in this journal. In this installment, we report on new identifications made in the interim, and offer a detailed analysis of four additional identified quotations, underlining their significance in historical and cross-cultural perspective.
Keywords: Mahayana; Hotan; The book of Zambasta